INTEGRATION OF BYZANTIUM – KYIVAN RUS ENAMELING TRADITIONS IN MODERN UKRAINIAN JEWELRY DESIGN - Барбалат, О. В.; Школьна, О. В. (Art and Design, 2020)
The purpose of this research is to understand the integration of the Byzantium-Kyivan Rus enameling traditions in modern Ukrainian jewelry design. The research is applied historical-cultural and artistic-design scientific approaches in combination with comparative and presentation methods. The results of the research prove the influence of Byzantine and Kyivan Rus enamel traditions on modern Ukrainian jewelry. The stylistic and artistic features of the items were examined on example of outstanding enamel jewelry of Byzantine and Kyivan Rus time. As a result the main principles of design requirements and quality of hot enamel jewelry were defined. This research highlights the principles which elites, as bearers of the highest spiritual values, used as guide lines when choosing and ordering jewelry products in ancient times. In order to understand the manufacturing and producing ancient enamel jewelry pieces the ancient jewelry centers are being studied and characterized in this research. We have analyzed the influence of Byzantium and Kievan Rus enameling traditions on the modern Ukrainian jewelry design. Also we studied how it changed with changing the conditions and intensity of manufacturing. Thanks to this research it has been explained how the Byzantine and Kievan Rus enameling traditions influenced modern Ukrainian jewelry design. The researchers were determined to create a symbiosis of modern scientific and technical methods with the ancient hot enamel techniques. This way the research reveals the newest methods of working with hot enamel that are on their initial phase in modern Ukrainian jewelry industry. The material of this research can be used in development of academic disciplines related to enameling techniques and jewelry design. It can be used as a source of inspiration for creating new conceptual jewelry collections using hot enamel. This research can help influence modern jewelry design in Ukraine. Results of this research can be used not only to popularize the Byzantine-Kievan Rus jewelry traditions in Ukraine but also for quality representation of Ukrainian jewelry art in the world